ショウワキチ ニオケル タイキチュウ CO2 ノ タンソ ドウイタイヒ δ13C ト サンソ ドウイタイヒ δ18O ノ ヘンカ - 村山, 昌平; ムラヤマ, ショウヘイ; 中澤, 高清; ナカザワ, タカキヨ; 青木, 周司; アオキ, シュウジ; 森本, 真司; モリモト, シンジ; Murayama, Shohei; Nakazawa, Takakiyo; Aoki, Shuhji; Morimoto, Shinji (1997)
P(論文) 1986年から南極昭和基地において大気中CO_2の安定同位体比の観測が行われてきた。δ^<13>Cの季節変化の振幅は平均0.04‰で非常に小さく, 秋に最高値, 春に最低値を示した。CO_2濃度の季節変化との比較から植物圏や海洋との交換及び化石燃料消費の影響を受けた大気が, 季節に依存する輸送過程を通して昭和基地に運ばれてくることによりCO_2濃度の季節変化を生じていることが示唆された。1986年から1990年の間の平均的なδ^<13>Cの増加率は, 約-0.02‰/年であった。δ^<13>Cの経年的な減少はCO_2濃度の増加率が大きいときに著しかった。CO_2濃度の経年変化との比較からCO_2濃度の経年変化に重畳したアノマリーは, 炭素循環における大気-生物圏間の交換の不均衡によって生じていることが示唆された。大気中CO_2のδ^<18>Oは, 冬に最低値, 夏に最高値を持つ顕著な季節変化を示した。この変化についても季節に依存する大気輸送過程が関係している可能性が示唆された。 Measurements of stable isotopic ratios of atmospheric CO_2 have been made at Syowa Station, Antarctica since 1986. The average peak-to-peak amplitude of the seasonal cycle of δ^<13>C was about 0.04‰ with the maximum in autumn and the minimum in spring. From comparison with the seasonal cycle of the CO_2 concentration, it was speculated that air with high CO_2 concentration influenced by exchange between the atmosphere and the biosphere and/or combustion of fossil fuel arrives at the station from late fall to early spring, while oceanic origin air with low CO_2 is transported from late spring to summer. The average increase rate of δ^<13>C of atmospheric CO_2 between 1986 and 1990 was about -0.02‰/year. Interannual variations of δ^<13>C, superimposed on the long-term trend, were also seen. These were approximately opposite in phase to those of the CO_2 concentration. The comparison of both interannual variations suggests that the principal cause could be an imbalance in the CO_2 exchange between the atmosphere and the biosphere. On the other hand, δ^<18>O of atmospheric CO_2 showed a clear seasonal cycle with the maximum in summer and minimum in winter, which may also be related to the seasonally-dependent atmospheric transport. departmental bulletin paper